1996
DOI: 10.1084/jem.183.6.2581
|View full text |Cite
|
Sign up to set email alerts
|

The role of gp130-mediated signals in osteoclast development: regulation of interleukin 11 production by osteoblasts and distribution of its receptor in bone marrow cultures.

Abstract: SummaryInterleukin (IL)-11 is a multifunctional cytokine whose role in osteoclast development has not been fully elucidated. We examined IL-11 production by primary osteoblasts and the effects of rat monoclonal anti-mouse glycoprotein 130 (gp130) antibody on osteoclast formation, using a coculture of mouse osteoblasts and bone marrow cells. IL-1, TNFoL, PGE2, parathyroid hormone (PTH) and 1cl,25-dihydroxyvitamin D3 (leq25(OH)2D3) similarly induced production of IL-11 by osteoblasts, but IL-6, IL-4, and TGF[3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(123 citation statements)
references
References 45 publications
8
114
1
Order By: Relevance
“…Similarly, we have previously reported that IL-11 is upregulated by both bone marrow stromal and endothelial cells in the presence of MM cells, 36 and other authors have found that MM cells stimulate OB IL-11 production. 37 IL-11 is a cytokine that is known to be critical for OCL formation under physiological conditions, 38,39 and to be involved in the development of osteolytic bone metastases in breast cancer patients. 40 --42 Interestingly, like other gp130 cytokines, it can induce OCL formation independently of RANKL.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we have previously reported that IL-11 is upregulated by both bone marrow stromal and endothelial cells in the presence of MM cells, 36 and other authors have found that MM cells stimulate OB IL-11 production. 37 IL-11 is a cytokine that is known to be critical for OCL formation under physiological conditions, 38,39 and to be involved in the development of osteolytic bone metastases in breast cancer patients. 40 --42 Interestingly, like other gp130 cytokines, it can induce OCL formation independently of RANKL.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, gp130 cytokine expression by cells within the bone remodelling unit are high throughout life (Table 1). Furthermore, the expression of gp130 cytokines by osteoblasts in particular, is strongly influenced by bone-active hormones and inflammatory cytokines including PTH, 1,25-dihydroxyvitamin D3, IL-1, estradiol and testosterone (22)(23)(24)(25). This indicates that gp130 cytokines, like RANKL, may play important paracrine roles to regulate bone formation and resorption within the bone remodelling unit during normal bone development, growth and remodelling.…”
Section: Gp130 Actions On the Skeletonmentioning
confidence: 99%
“…The pro-osteoclastic gp130 cytokines generally stimulate osteoclast formation by acting on osteoblast lineage cells to enhance expression of the key osteoclastogenic factor RANKL, and by reducing osteoblastic expression of its inhibitor OPG (29)(30)(31). Furthermore, studies using the gp130 knockout mouse, and a gp130 neutralising antibody have demonstrated that a gp130-dependent pathway is involved in the stimulation of osteoclast formation by other factors, including 1,25-dihydroxyvitamin D3, parathyroid hormone (PTH), and inflammatory cytokines such as IL-1, (22,32). Neutralising antibody studies also indicated that PTH-stimulated osteoclast formation requires at least IL-6R (24) and IL-11 (33).…”
Section: Gp130 Cytokine Action On Osteoclastsmentioning
confidence: 99%
“…The murine IL-11R␣ 1 gene is expressed at relatively low abundance in a broad spectrum of tissues including bone marrow, spleen, thymus, lung, bladder, heart, brain, kidney, muscle, salivary gland, small and large intestine, ovary, testis and uterus as well as a number of primary cell types such as macrophages, osteoblasts and osteoclasts. 4,20,21 Expression of the IL-11R␣ 2 gene is restricted to the testis, lymph node and thymus. 19 The human IL-11R␣ chain shares 85% nucleotide identity and 84% amino acid identity with the murine genes.…”
Section: Il-11 Receptormentioning
confidence: 99%